Parental and Teacher Perspectives on the Importance of Physical Education inSchool Learning - Deni Nugraha; Mudjihartono; Agus Gumilar (Universitas Negeri Semarang, 2026)
Physical Education, Sports, and Health (PE) plays an important role in supporting students' physical, mental, and social development; however, in practice it is still frequently regarded as a secondary subject compared to academic subjects. This study aims to analyze teachers' and parents' perceptions of the importance of PE in school learning and to identify whether there are differences in perception between both groups. This study employed a quantitative approach with a descriptive design, involving 60 respondents consisting of 30 teachers and 30 parents selected using purposive sampling. The research instrument was a closed questionnaire with a Likert scale, while data analysis techniques included descriptive statistics and an independent sample t-test. The results showed thatboth teachers' and parents' perceptions of the importance of PE were in the positive category, with teachers' mean scores higher than those of parents. However, the t-test results indicated no significant difference between the two groups. These findings suggest that teachers and parents fundamentally share relatively aligned views regarding the urgency of PE in learning. Thus, this study concludes that although descriptive differences exist, the shared perceptions between teachers and parents open opportunities to strengthen collaboration in supporting PE learning in schools more optimally.